The Influence of Corporate Governance Mechanisms on Financial Reporting Fraud (A Study on Property & Real Estate Sector Companies Listed on IDX in the Years 2018-2022) - Dewi Aryani; Afrizal; Yuliusman (PT FORMOSA CENDEKIA GLOBAL, 2023)
The objective of this study is to investigate the impact of corporate governance mechanisms on financial statement fraud. The study focuses on board of commissioners, independent commissioners, managerial ownership, institutional ownership, and audit committees. Purposive sampling is used, targeting property and real estate companies listed on the Indonesian Stock Exchange from 2018 to 2022. The sample consists of 16 companies, resulting in a total of 80 data points over a 5-year period. Data analysis techniques include descriptive statistics and logistic regression analysis using SPSS software version 26. The findings reveal that the audit committee plays a positive role in preventing financial statement fraud, while the other factors examined do not exhibit significant influence